(untitled) (Jurnal Teknodik, 2025)
The problem addressed in this study is how the Center for Da’wah Technology Development (PPTD) plays a strategic role in equipping students of the Faculty of Da’wah and Communication at UIN Sunan Kalijaga with hard skills and soft skills. The purpose of this research is to examine the strategic role of PPTD in preparing students with these competencies. The paradigm employed in this study is phenomenological with a descriptive approach. The type of research used is qualitative. The study was conducted from May 2 to May 28, 2025. Data collection techniques included observation and documentation of community activities, program outputs, and student portfolios in photography, television, and radio. Data analysis was carried out using Talcott Parsons’ AGIL scheme (Adaptation, Goal Attainment, Integration, and Latency). The findings reveal that students adapt through the use of modern technology, achieve clearly defined goals, establish collaboration across communities, and maintain established patterns through training and workshops that have been effectively implemented. The conclusion suggests that PPTD has effectively equipped students with both hard and soft skills through various community-based activities designed in response to developments in the media industry.